METODE CALISNA HIFAL MENINGKATKAN KEMAMPUAN MEMBACA ANAK USIA DINI DI ERA PANDEMI COVID-19 - Fatlud Rozi (JEA (Jurnal Edukasi AUD), 2022)
Children are successors on earth, every child born has various abilities. The impact of the Covid-19 pandemic has resulted in parents not optimally assisting their children in learning, especially learning to read. Reading is an important component thatmust be developed for early childhood. The need for an effective method to trigger talent, interest in early childhood development in reading and understanding their environment. For this reason, the calisna hifal method creates a leraning pattern that is interactive, active and collaborative. This study uses a descriptive qualitative research method by examining 30 children aged 0-8 years for 10 months and the results of the analysis conclude that the calisna hifal method can effectively improve early childhood reading skills in the Covid-19 pandemic era.